2022
DOI: 10.21608/asnj.2022.133103.1360
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors assessment of ocular surface disorders among adult critically ill patients

Abstract: Ocular complications are common in the critical care setting but are frequently missed due to the focus on life-saving organ support. In critically ill patients, normal eye protection mechanisms, such as tear production, blinking, and keeping the eye closed, are impaired. This study aims to: assess risk factors for ocular surface disorders among adult critically ill patients. Design: Exploratory research design. This study was carried in intensive care units at Assiut university hospital. Subjects: A convenien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It can result in visual impairment and a lower quality of life by causing eye dryness, infection, ulcerations, even perforation, and iatrogenic mechanical corneal damage. 31 This report supports the finding of the study "A bundle improves eye care in PICU" by McCall et al, which found that longer critical care stay and partial eyelid closure were risk factors for the development of corneal surface abnormalities. 32 Additionally, it was discovered by Kuruvilla et al that closing the eyelids acts as a mechanical protection against corneal exposure and drying.…”
Section: Assessment Of Eyelid Closuresupporting
confidence: 90%
See 1 more Smart Citation
“…It can result in visual impairment and a lower quality of life by causing eye dryness, infection, ulcerations, even perforation, and iatrogenic mechanical corneal damage. 31 This report supports the finding of the study "A bundle improves eye care in PICU" by McCall et al, which found that longer critical care stay and partial eyelid closure were risk factors for the development of corneal surface abnormalities. 32 Additionally, it was discovered by Kuruvilla et al that closing the eyelids acts as a mechanical protection against corneal exposure and drying.…”
Section: Assessment Of Eyelid Closuresupporting
confidence: 90%
“…They did not have spontaneous eye opening, and the frequency of blinking was limited. It can result in visual impairment and a lower quality of life by causing eye dryness, infection, ulcerations, even perforation, and iatrogenic mechanical corneal damage 31. This report supports the finding of the study “A bundle improves eye care in PICU” by McCall et al, which found that longer critical care stay and partial eyelid closure were risk factors for the development of corneal surface abnormalities 32.…”
Section: Discussionsupporting
confidence: 79%
“…Such exposure may result in increased tear film evaporation and dryness of the ocular surface ( 28 ) . Study points out in its results the exposure of the eyeball as the main risk factor for alterations of the ocular surface ( 1 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they generally require complex care, ventilatory assistance, invasive procedures and the use of various medications, such as sedatives and neuromuscular blockers to maintain clinical therapy and vital parameters, which can lead to ocular changes. In this way, the importance of eye care is emphasized in order to avoid complications on the ocular surface until the possible evolution to vision loss ( 1 , 2 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Assim, geralmente, necessitam de cuidados complexos, assistência ventilatória, procedimentos invasivos e uso de variados medicamentos, como sedativos e bloqueadores neuromusculares, para manutenção da terapêutica clínica e dos parâmetros vitais, que podem levar a alterações oculares. Dessa forma, ressalta-se a importância do cuidado ocular no sentido de evitar complicações na superfície ocular até a possível evolução para a perda da visão (1)(2) .…”
Section: Introductionunclassified